From Symbionts to Societies: How Wood Resources Have Shaped Insect Sociality - Dillard, Jacqueline; Benbow, Mark Eric (Frontiers in Ecology and Evolution, 2020)
Sociality has independently arisen in several wood-dwelling insect lineages, yet little is understood about how the properties of decaying logs have favored the evolution of cooperative social groups. Here we evaluate the current literature on wood-dwelling social insects to identify the structural, nutritional, and microbial properties of decaying logs that have led to the repeated evolution of social behavior. Wood-tissue is structural resilient, and thus provided an enclosed, defensible nest site for early wood-feeding insect groups. This structural stability enabled the long-term persistence of family groups, and was likely a key feature in the transition toward more complex eusocial societies. The resilient structure and relatively poor nutritional quality of wood also likely provided a stable environment for the evolution of complex mutualisms with prokaryote and fungal symbionts to digest this resource. Parental care likely evolved as a means to protect the valuable nest site and ensure adequate nutrition for offspring in this environment by allowing parents to both provision and transfer microbial symbionts to offspring. Pathogenic microbes are also abundant in nests constructed in wood-tissue, and social adaptations such as allogrooming and nest maintenance may have evolved in response to microbial invaders. In general, the dynamic relationships between insects, microbes, and the wood-tissue that they inhabit was a critical component in the evolution of sociality in this habitat.